Rancangan Alat Pengisi Baterai Gadget Dengan Menggunakan Pembangkit Listrik Tenaga Surya - Titi Ratnasari; Tasdik Darmana; Jumiati Jumiati; Arif Sutyanegara; M Kahfi Fachelinno; Tri Purnama Putra; Ianatut Toyyibah (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2016)
Gadget is an innovation of the latest technology with better ability, the shape can be a smartphone, laptop, computers and others. To be able to operate the gadgets required in the form of battery power. When the gadget runs out of power often confused gadget users to charge the battery because in certain conditions. The purpose of this study was to design a tool to help users gadgets run out of battery in a way that is easy and affordable. This study uses the method of literature review, interviews, designing, manufacturing project, test and produce a prototype, using solar panels as power efficient supplier. When the solar panels convert solar energy into electrical energy which is stored in Cell Battery then stabilize by the stabilizer circuit and power supplied via the USB Cable and finally the battery can be charged. This function helps the user gadget in charging the battery. Not only the battery charge, the tool also serves 220 Volt electrical energy saving and environmental advisor gadget users. Gadget users can use these tools for free as there are in public facilities. The results showed that the design of the charger gadget It helps the students and the community in solving the problem of charging the battery of the gadget.